81-y2=5

Divide 8 by 1.

8-y2=5

Subtract 8 from both sides of the equation.

-y2=5-8

Subtract 8 from 5.

-y2=-3

-y2=-3

Multiply both sides of the equation by -2.

-2⋅(-y2)=-2⋅-3

Simplify -2⋅(-y2).

Cancel the common factor of 2.

Move the leading negative in -y2 into the numerator.

-2⋅-y2=-2⋅-3

Factor 2 out of -2.

2(-1)⋅-y2=-2⋅-3

Cancel the common factor.

2⋅-1⋅-y2=-2⋅-3

Rewrite the expression.

-1⋅(-y)=-2⋅-3

-1⋅(-y)=-2⋅-3

Multiply.

Multiply -1 by -1.

1⋅y=-2⋅-3

Multiply y by 1.

y=-2⋅-3

y=-2⋅-3

y=-2⋅-3

Multiply -2 by -3.

y=6

y=6

Solve for y 8/1-y/2=5